Glaciolacustrine sediments and Neoglacial history of the Chephren Lake basin, Banff National Park, Alberta - Dirszowsky, Randy; Desloges, Joseph (Géographie physique et Quaternaire, 1997)
AbstractModern and historical sedimentation in Chephren Lake are examined in order to assess the relations between glacier activity, sediment production, and the lacustrine depositional record. Bottom sediment data and lake morphology indicate that sediments in the distal part of the lake primarily settled from suspension and that glaciers are the most important source. A 4.3 m core obtained from the distal sediments reveals that accumulation of fine, glacially-derived material has increased since at least 2 420 BP. Simple geochemical indicators reflect this and support regional evidence for progressive (though punctuated) climate deterioration through the Neoglacial period. Distinct rhythmite sequences (especially beginning ca. 3 460, 2 330, 1 470 and 530 BP) are thought to represent minor glacier retreats which help define separate phases of Neoglacial advance identified by previous workers. In contrast, increasing slope stability indicated by a reduction in graded sand and clast facies may be specific to slopes overlooking the coring site.